Pengaruh Harga Minyak Bumi, Harga Bahan Baku Plastik Terhadap Return On Asset Pada Perusahaan Penghasil Bahan Baku Plastik - Denny Saputera (Universitas Serang Raya, 2019)
This study focuses on the effect of petroleum prices, the price of plastic raw materials on return on assets in companies producing plastic raw materials in Indonesia. This study aims to determine the high growth return on assets, making the companies that produce plastic raw materials will get the maximum benefit from the use or turnover of assets owned. If directly related to the relationship between the growth of petroleum prices, the growth of the plastic industry and growth return on assets has a relationship, namely plastic raw materials derived from petroleum, where the price of plastic raw materials becomes very sensitive to fluctuations in oil price movements which will affect the company's profitability. The Independent Variables used are Petroleum Prices, Naphtha Prices, Ethylene Prices, Polyethylene Prices, Ethylene Glycol Prices, Polyvinyl Chloride Prices, Propylene Prices and Polyproylene Prices. The analytical method used is multiple linear regression using the help of SPSS 20 software. The results of this study can be concluded that Ethylene Prices and Ethylene Glycol Prices have an influence on return on assets.